Experimental and Computational Aspects of Electrochemical Reflection Anisotropy Spectroscopy: A Review. Issue 8 (22nd March 2023) - Guidat, Margot; Löw, Mario; Kölbach, Moritz; Kim, Jongmin; May, Matthias M.
Abstract: Electrode/electrolyte interfaces play a crucial role in many electrochemical energy conversion and storage technologies. Hence, a deep understanding of the interfacial structure, energetic alignment and processes is of high relevance and has triggered the development of a number of in situ and operando techniques. One approach for gaining information about the change in surface chemistry and structure on an atomic scale is reflection anisotropy spectroscopy (RAS). This review presents and discusses the continuing effort to develop RAS as an in situ optical probe for solid‐liquid interfaces under applied potentials. Experimental and computational basic principles are presented and key challenges of electrochemical RAS are highlighted. Furthermore, we exemplarily demonstrate the potential of the method for spectroelectrochemistry, focusing on indium phosphide‐ and gold‐aqueous electrolyte interfaces as exemplary case studies, and outline research directions for battery systems. Abstract : Understanding and controlling highly ordered electrochemical interfaces can be achieved by reflection anisotropy spectroscopy in parallel with electrochemical measurements. An in‐depth understanding of experimental results from this spectroelectrochemical approach does, however, typically require a combination with computational spectroscopy.